Influence Of Product Quality, Promotion0and Product Variations On Kanzler Product Purchase Decisions: The Influence Of Product Quality, Promotion And Product Variation On Kanzler Product Purchasing Decisions - Fardiansyah, M. Fiqh; Farida, Lailatul (Universitas Islam Lamongan, 2023)
This research was conducted with the aim of finding out the influence of product quality, promotion and product variety on purchasing decisions for PT Macroprima Pangutama (Cimory Group) Kanzler products, a study at UIN Maulana Malik Ibrahim Malang, using primary data with a proportional sampling method, thus containing 119 respondents. This research uses SPSS version 25. The research uses multiple linear regression analysis techniques. The results of the research show that there is a simultaneous influence on the variables Product Quality, Promotion and Product Variety which influence purchasing decisions.